Justification of the Wood Polymer Material Application Conditions - Horbachova O. Yu.; Tsapko Yu. V.; Tsarenko Y.; Mazurchuk S. M.; Kasiyanchuk I. O. (Журнал інженерних наук)
The production of heat-insulating materials based on wood was analyzed in this paper. The expediency and efficiency of using wood waste were established. A study of the operational properties of the sample obtained from wood shavings polymerized with mixtures of polyester and epoxy resins was carried out. It was proven that the process’s primary regulator is the material’s density and porosity. Also, an increase in humidity and wetting reduces heat-insulating indicators. Based on thermophysical dependences, the thermal insulation properties of the samples were calculated. Moreover, it was established that the thermal conductivity does not exceed 0.21·10–6 m2/s, and the thermal conductivity of the sample – 2.85·10–3 W/(m·K). Therefore, these products can be classified as heat-insulating materials. A through-thickness compressive strength study showed that the wood shavings and polyester resin material are more fragile, and the strength limit was reduced by more than 1.2 times compared to the epoxy resin-based material. The moisture absorption results showed that a heat-insulating product made of shavings polymerized with polyester resin. Moisture absorption was 5 % after 90 days of exposure to water. On the other hand, the heat-insulating products made of shavings with epoxy resin of 4.41 % showed their resistance to moisture absorption.